Dynamics of China-ASEAN Economic Relations: A Strategic Alliance and Regional Integration in the 21st Century - Annisa, Nabila; Rofi, Muhammad Hasan; Rohimat, Tiko; Kusyaeri, Irlani Alifah (Candidate: Jurnal Sains Politik, 2023)
This study investigates the multifaceted nature of the China-ASEAN economic cooperation, exploring its impact on global trade and financial sectors. It delves into the dynamics of this relationship, highlighting the strategic partnership and trade agreements like the ASEAN-China Free Trade Agreement (ACFTA) and the Regional Comprehensive Economic Partnership (RCEP). The research adopts a qualitative approach, analyzing data from various sources including academic journals and government documents to offer an in-depth understanding of the evolving China-ASEAN economic collaboration. Key findings illustrate China's growing investment in ASEAN, especially in infrastructure, manufacturing, and technology, fostering mutual economic growth and creating job opportunities. The Belt and Road Initiative (BRI) by China emerges as a significant factor in enhancing regional connectivity. Furthermore, the study explores the cooperation in innovation and technology between China and ASEAN, emphasizing the potential for technology transfer and joint research. The study underscores the bright prospects of the China-ASEAN economic partnership, emphasizing its role in shaping the global trade landscape. It also acknowledges the need to address challenges like political issues, economic competition, and environmental concerns to ensure a sustainable and mutually beneficial partnership. Â 